The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0231717
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding and species delimitation of the Old World tooth-carps, family Aphaniidae Hoedeman, 1949 (Teleostei: Cyprinodontiformes)

Abstract: The fishes, which have currently named Aphanius Nardo, 1827 are the relict of the ancient ichthyofauna of the Tethys Sea. For a long time since 1827, the genus name has been subjected to revision by several researchers using mainly morphological features. Until recently, no comprehensive single-or multi-locus DNA barcoding study has been conducted on whole members of the family Aphaniidae. In the present study, by applying four conceptually different molecular species delimitation methods, including one distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 101 publications
9
23
0
Order By: Relevance
“…Moreover, Ferrito et al (2009) showed that the scale surface microstructures and the lepidonts on the circuli crests of Aphanius species (see Esmaeili, Teimori, Zarei, & Sayyadzadeh, 2020 well as environmental parameters would affect scale morphology (Ibáñez, 2014;Swain & Foote, 1999;Teimori, 2018). Therefore, the characteristics of scale morphology may not be applicable to infer the taxonomic relationships of some fish groups in their local distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ferrito et al (2009) showed that the scale surface microstructures and the lepidonts on the circuli crests of Aphanius species (see Esmaeili, Teimori, Zarei, & Sayyadzadeh, 2020 well as environmental parameters would affect scale morphology (Ibáñez, 2014;Swain & Foote, 1999;Teimori, 2018). Therefore, the characteristics of scale morphology may not be applicable to infer the taxonomic relationships of some fish groups in their local distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a sinuous shape of the epural is absent in A. furcatus and it is also absent in the related Paraphanius mento (this study and Teimori et al., 2014). However, Costa (2012a) reported this character also for Aphanius isfahanensis , and two of the Anatolian Aphanius species, which are not closely related according to molecular studies (Esmaeili et al., 2020; Hrbek & Meyer, 2003). It could be that this trait has evolved convergently in different clades of the Aphaniidae.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies by Freyhof, Weissenbacher, and Geiger (2017), Teimori, Esmaeili, Hamidan, and Reichenbacher (2018) and Esmaeili et al. (2020) indicate that A. dispar includes four species ( A. dispar , A. hormuzensis Teimori et al., 2018, A. kruppi Freyhof et al., 2017 , A. stoliczkanus (Day, 1872)), which, together with further five species ( A. furcatus Teimori, Esmaeili, Erpenbeck, & Reichenbacher, 2014, A. ginaonis (Holly, 1929), A. richardsoni (Boulenger, 1907), A. sirhani Villwock et al., 1983, A. stiassnyae (Getahun & Lazara, 2001)) comprise the genus Aphaniops .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The members of the family Aphaniidae demonstrate great biological diversity in the old world (Esmaeili et al, 2020). Similar to other killifishes, they have a relatively short generation period, and high endurance in the wild and laboratory conditions (Evans et al, 2011; Schartl, 2014).…”
Section: Introductionmentioning
confidence: 99%